ANALISIS STRATEGI PRODUSER MUSIK DANSA ELEKTRONIK DALAM MEMASARKAN KARYA SECARA MANDIRI DI ERA MODERN: ANALISIS STRATEGI PRODUSER MUSIK DANSA ELEKTRONIK DALAM MEMASARKAN KARYA SECARA MANDIRI DI ERA MODERN - Andre, Andre Pratama; Sholikhah, Afifatus (Universitas Nahdlatul Ulama Sidoarjo, 2025)
Electronic Dance Music or what we usually know as (EDM) is a genre of music that applies electronic technology to produce musical compositions dominated by dance rhythms and synthetic sounds. Since its emergence at the end of the 20th century, EDM has grown rapidly and includes various subgenres such as house, techno, trance, dubstep, and drum and bass. Using devices such as synthesizers, drum machines, and digital music production software, EDM creates dynamic and energetic audio experiences, often produced for consumption in nightclubs, music festivals, and digital platforms. EDM is not only an integral part of global music culture, but also influences social trends, consumer behavior, and the entertainment industry at large. Due to the rapid technology in this era, someone can easily make music (EDM) on their laptop or PC, but even so, there are things that need to be considered when someone has made music (EDM), namely marketing their work to the public, which is marketing something. The results we make or produce are an important aspect where if we don't market something we make then no one will enjoy or feel the results or work we make. Marketing a product or work requires several rules and attention as well as strategies so that the marketing achieves satisfactory and successful results. The aim of this research is to discuss the importance of careful marketing planning in supporting the successful marketing of works of art, as well as examining the various approaches used by music producers to market their work independently effectively in the digital era. The research that I use uses interview and documentation research, the research method is descriptive qualitative research, where I as a researcher try to describe the phenomena observed in a detailed and systematic way and provide a more holistic insight into the topic being researched with a source as a producer. The music is DFAN which comes from Bekasi, Indonesia.